Does long-term profound inhibition of gastric acid secretion increase the risk of ECL cell-derived tumors in man?. (2nd July 2016) - Waldum, Helge L.; Hauso, Øyvind; Brenna, Eiliv; Qvigstad, Gunnar; Fossmark, Reidar
Abstract: Objective: Since the description of ECL cell-derived tumors in rodents after long-term profound acid inhibition inducing hypergastrinemia, there has been concern that proton pump inhibitors (PPIs) could also do that in man. The recent description of a Spanish family with gastric ECL cell tumors at the age of about 30 years secondary to a defect in the proton pump due to mutation in the ATP4A gene clearly shows that hypergastrinemia alone also is sufficient to induce ECL cell neoplasia in man. The present review aims to evaluate the risk of gastric neoplasia secondary to gastric acid inhibition. Methods: Literature (MEDLINE) was searched for the role of the ECL cell in gastric carcinogenesis in animals and man in general and particularly secondary to long-term inhibition of acid secretion. Results: An important proportion of patients treated with PPI develops hypergastrinemia causing ECL cell hyperplasia and the first descriptions of ECL cell carcinoids secondary to PPI have been reported. The role of the ECL cell has hitherto been under estimated in gastric carcinogenesis in man where for instance the signet ring cell type of gastric carcinoma seems to originate from the ECL cell. Conclusions: The first two of three steps in rodent ECL cell carcinogenesis (hyperplasia, carcinoid, and carcinoma) secondary to PPI dosing, have been described for man. It is every reason to believe that the final step, gastric carcinoma, will develop also in man. Clinical decisions should be based not only on so-called evidence based medicine, but also on physiological knowledge and animal studies.